(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The purpose of this research work was to improve the aqueous solubility and dissolution rate of carbamzepine by solid dispersion (SD) technique. Polyethylene Glycol 6000, Polyethylene Glycol 4000, poloxamer 407 and povidone k 30 were used as water soluble polymer for preparing solid dispersion. Solid dispersions were prepared by the solvent evaporation method. Methanol was used as solvent. Drug-carrier physical mixtures were also prepared to compare the rate of dissolution. Effects of different polymer were studied for solid dispersion formulation as well as physical mixtures. A significant increase, almost 100% in the release of carbamzepine within one hour was observed in case of the solid dispersion formulations containing PEG 6000 in combination with poloxamer 407 at the ratio of 1: 1: 5. By far, Fourier Transform Infrared (FTIR) spectroscopic studies showed the stability of carbamazepine and absence of well-defined drug-polymer interactions. The Scanning Electron Microscopy (SEM) studies indicated that the incorporation of polymers transforms crystalline carbamazepine into amorphous state, thus increasing its solubility and dissolution rate. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 213-220